47 ROLE OF ACYLGLYCEROL KINASE IN LYSOPHOSPHATIDIC ACID-INDUCED TRANSACTIVATION OF EPIDERMAL GROWTH FACTOR RECEPTOR AND EXPRESSION OF CYCLOOXYGENASE 2 AND INTERLEUKIN-8 IN PRIMARY HUMAN BRONCHIAL EPITHELIAL CELLS. (1st March 2007) - Kalari, S.; Zhao, Y.; Berdyshev, E.; Usatyuk, P. V.; He, D.; Natarajan, V.
Abstract : Rationale: Acylglycerol kinase (AGK) phosphorylates monoacylglycerol and diacylglycerol to form potent lipid second messengers, lysophosphatidic acid (LPA) and phosphatidic acid (PA), respectively. We have shown earlier that LPA induces transactivation of epidermal growth factor receptor (EGF-R) in human bronchial epithelial cells (HBEpCs). Here we provide evidence for the role of AGK in LPA-mediated expressions of COX-2 and IL-8 involving transactivation of EGF-R in HBEpCs. Methods/Results: Expression of AGK in HBEpCs was detected by real-time PCR. The full-length cDNA of AGK was cloned from HBEpCs and inserted into lentiviral vector with V5-tag on the C-terminal. The overexpressed AGK was mainly localized in mitochondria as determined by immunofluorescence and confocal microscopy. Overexpression of lenti-AGK wild type increased intracellular LPA production (≈1.8-fold), enhanced LPA-mediated phosphorylation of EGF-R and ERK1/2, and stimulated expression of COX-2 and IL-8 secretion. Further, down-regulation of AGK expression by AGK siRNA decreased intracellular LPA levels by ≈2-fold and attenuated LPA-induced tyrosine phosphorylation of EGF-R and tyrosine/threonine phosphorylation of ERK1/2, COX-2 expression, and IL-8 secretion. Conclusions: These results suggest a role for AGK in LPA-mediated activation of COX-2 expression and IL-8 secretion via EGF-R transactivation and signal transduction in HBEpCs. Thus, AGK-mediated intracellular LPA production and signaling may play a potential role in innate immunity and airway remodeling during inflammation. Supported by NIH grant HL 71152 and 79396 to V.N.